Death and survival in Streptococcus mutans: differing outcomes of a quorum-sensing signaling peptide - Leung, Vincent; Dufour, Delphine; Lévesque, Céline M. (Frontiers in Microbiology, 2015)
Bacteria are considered ‘social’ organisms able to communicate with one another using small hormone-like molecules (pheromones) in a process called quorum-sensing. These signalling molecules increase in concentration as a function of bacterial cell density. For most human pathogens, quorum-sensing is critical for virulence and biofilm formation, and the opportunity to interfere with bacterial quorum-sensing could provide a sophisticated means for manipulating the composition of pathogenic biofilms, and possibly eradicating the infection. Streptococcus mutans is a well-characterized resident of the dental plaque biofilm, and is the major pathogen of dental caries (tooth decay). In S. mutans, its CSP quorum-sensing signalling peptide does not act as a classical quorum-sensing signal by accumulating passively in proportion to cell density. In fact, particular stresses such as those encountered in the oral cavity, induces the production of the CSP pheromone, suggesting that the pheromone most probably functions as a stress-inducible alarmone by triggering the signalling to the bacterial population to initiate an adaptive response that results in different phenotypic outcomes. This mini-review discusses two different CSP-induced phenotypes, bacterial ‘suicide’ and dormancy, and the underlying mechanisms by which S. mutans utilizes the same quorum-sensing signalling peptide to regulate two opposite phenotypes.